Sex Differences in Abnormal Intrinsic Functional Connectivity After Acute Mild Traumatic Brain Injury - Wang, Shan; Hu, Liuxun; Cao, Jieli; Huang, Wenmin; Sun, Chuanzhu; Zheng, Dongdong; Wang, Zhuonan; Gan, Shuoqiu; Niu, Xuan; Gu, Chenghui; Bai, Guanghui; Ye, Limei; et al. (Frontiers in Neural Circuits, 2018)
Mild traumatic brain injury (TBI) is considered to induce abnormal intrinsic functional connectivity within resting-state networks. The objective of this study was to estimate the role of sex in intrinsic functional connectivity after acute mild TBI. We recruited a cohort of 54 patients (27 males and 27 females with mild TBI within 7 days post-injury) from the emergency department and 34 age-, education-matched healthy controls (17 males and 17 females). On the clinical scales, there were no statistically significant differences between males and females in either control group or mild TBI group. To detect whether there was abnormal sex difference on functional connectivity in resting state networks (RSNs), we performed independent component analysis (ICA) and a dual regression approach to investigate the between-subject voxel-wise comparisons of functional connectivity within seven selected RSNs. Compared to female patients, male patients showed increased intrinsic functional connectivity in motor network, ventral stream network, executive function network, cerebellum network, and decreased connectivity in visual network. Further analysis demonstrated a positive correlation between the functional connectivity in executive function network and insomnia severity index scores in male patients (r = 0.515, P = 0.006). The abnormality of the functional connectivity of RSNs in acute mild TBI showed the possibility of brain recombination after trauma, mainly concerning male-specific.